Quantitative Analytical Model of the Formation Damage by Gel Particles - Elsharafi, Mahmoud; Saleh, Laila; Bai, Baojun (Journal of Technology Innovations in Renewable Energy, 2017)
Formation damage by gel particles has become one of the most important problems in mature reservoirs. The objective of the quantitative analytical model is to identify an analytical model to the best fit of the preformed particle gels (PPGs) filtration test results. This work will analyze the experiments results of low permeability core samples to evaluate the effect of various brine concentrations and particle sizes. This study used a linear analytical model relationship between cumulative volumes versus filtration time with a good fits result. Linear curve equations for the best fitting equation was obtained. According to quantitative analytical model for all of our filtration tests, the cumulative filtration test volume (Vcf) was explained in this paper. Quantitative analytical model results showed the value of the slop m increases as the injection pressure increases. Compared with the experiments, the results show that, if the value of the intercept b > 2 the damage occurred because the gel particles invasion started into the core surface. Results from the quantitative analytical model were indicated to have a good fitting with almost all of the experimental results. It is the first time to use quantitative analytical model to analysis the formation damage by the PPGs. The results can be used to select the best gel treatment design.